A Report and Analysis of the Accountancy Faculty Recruiting Surveys of 1975-1978. - Mehl, Arthur G.; Lammers, Lucille E. (The Accounting Review, 1979)
Abstract In May of 1975, 1976, 1977, and 1978 a faculty-recruiting questionnaire was mailed to accounting program administrators of schools holding membership in the American Assembly of Collegiate Schools of Business. The purpose of the study was to determine the supply of, and demand for, accounting faculty along with other pertinent information concerning the recruitment of new faculty. A discussion of the 1978 findings along with an analysis of the four-year trend are presented. Ample evidence of a faculty shortage is provided. There is an insufficient number of professional teachers to meet classroom staffing needs. This, in turn, may be a threat to the quality of accounting education. Exhibits are in comparative form for the four years and show details of the salaries offered new assistant professors, the availability of summer teaching and summer research, and the types of courses and number of course hours taught by the new assistant professors. The four-year trend displayed in the exhibits is briefly discussed.